Infrastruktury (dějin) umění sborník ze VII. sjezdu historiků a historiček umění v Ústí nad Labem - Bartlová, Anežka 1988-; Buddeus, Hana ca. 20./21.Jh (Fakultou umění a designu Univerzity Jana Evangelisty Purkyně, 2022)
Infrastructures present one of the central themes in contemporary art. What is their place in the discipline of art history? The proceedings from the 7th congress of art historians held in September 2021 in Ústí nad Labem discusses the topic in five chapters uncovering the mechanisms of collecting, exhibiting, and reproducing art. In addition, the volume contains texts on the conservation and renovation of artistic monuments. The focus is on the temporally and locally conditioned context: everything that surrounds the work and constitutes its material structure, enables or directly shapes its existence, preserves it in time, and brings attention to it.
Keywords: Infrastruktur; Kunst; dějiny umění; muzea umění / Česko; umělecké sbírky / Česko; reprodukce uměleckých děl; umělecké výstavy / Česko; zprostředkování umění; umělecké vzdělávání; restaurování památek; history of art; art museums / Czechia; art collections / Czechia; fine art reproductions; art exhibitions / Czechia; art mediation; art education; antiquities restoration; sborníky konferencí; proceedings of conferences; Konferenzschrift -- 2021 -- Ústí nad Labem